Three-dimensional simulation of silted-up dam-break flow striking a rigid structure. (1st October 2022) - Meng, Wenkang; Yu, Ching-hao; Li, Jia; An, Ruidong
Abstract: Different from the clear water dam-break flow, flow patterns and multiphase interactions of the silted-up dam-break flow are always more complicated, hence it may lead to more potential hazards. In this paper, three-dimensional numerical simulations of the silted-up dam-break flow striking a rigid structure are carried out by using a proposed Eulerian-Eulerian multiphase model, coupling kinetic particle theory (KPT) and computational fluid dynamics (CFD). The coupled level set and volume of fluid (CLSVOF) method and an advection-diffusion equation are employed to capture the air-water interface and sediment transport, respectively. Modified momentum equations suitable to the two-fluid method are solved by OpenFOAM, an open-source package based on fixed unstructured mesh. Furthermore, rheology-based constitutive equations of sediment are also taken into account for the simulation of scouring and deposition. The results of the benchmark case agree well with those in published papers, which demonstrates that the proposed model can effectively simulate gravity-dominated collapse flow while considering the multi-interface capturing problems. Subsequently, the Eulerian-Eulerian multiphase model is used to reproduce the problems of three-dimensional silted-up dam-break flow striking a rigid structure, mainly focusing on the aspects of front propagation, violent free surface deformation, sediment movement, dynamic pressure loads and sediment deposition. Four scenarios in the downstream are considered: dry bed, a tailwater sill, a short obstacle, and a vertical cylinder. In addition, the effects of the height of the silted-up sediment on dam-break flow are investigated numerically. Highlights: A proposed Eulerian-Eulerian multiphase model coupled kinetic particle theory and computational fluid dynamics. A two-liquid CLSVOF method was employed to capture the air-water interface and the sediment interface, respectively. Rheology-based constitutive equations of sediment were also taken into account for the simulation of scouring and deposition. The proposed method was used for simulation of silted-up dam-break flow striking a rigid structure.